Masked polycythemia vera manifested by splanchnic venous thrombosis during pregnancy: a clinical case - M. Yu. Nadinskaia; Kh. B. Kodzoeva; M. A. Sokolova; S. V. Apresyan; E. Yu. Kryzhanovskaya; A. A. Shchukina; E. A. Kitsenko (IRBIS LLC, 2022)
Ph-negative myeloproliferative disorders such as polycythemia vera (PV), essential thrombocythemia, and primary myelofibrosis are rare clonal hematopoietic diseases that typically occur at age over 50. Only 10-15% of PV cases are diagnosed during the reproductive years, most commonly manifested as splanchnic venous thrombosis (SVT). Here, we demonstrate a case of a 6-weeks pregnant woman with a history of stillbirth and miscarriage presented with SVT. A terminal ileal resection and right hemicolectomy were performed, as well as the appointment of low molecular weight heparin in the postoperative period was initiated that allowed the patient to continue the pregnancy and deliver a child. The JAK2 V617F mutation was detected and masked PV was diagnosed according to bone marrow findings. In this article, we discuss the etiology of SVT in adults and effect of JAK2 V617F mutation on pregnancy outcomes as well as summarize current knowledge about pregnancy outcomes in PV.